Bras levés – Bras baissés - Sur une succession de gestes dans l’histoire de l’art - Paul Bernard-Nouraud (Interfaces)
Among the countless gestures that one can find in Art History, two of them at least can be qualified as limit-gestures: raising one’s arms, and letting them down. If they are so, it is because contrary to the pointing finger that one can see in Michelangelo’s representations of Moses, God or Adam, the raising and lowering of arms are disordered gestures. Their meaning is unclear, and, eventually, they only designate the bodies of those who produce such gestures. Considering Antoine Watteau’s Gilles and Francisco Goya’s 3rd of May 1808, this essay intends to summarize how this gestural limit in modern Art History lasted at least until Édouard Manet’s oeuvre.